Paroxysmal atrial fibrillation with high vs. low arrhythmia burden: atrial remodelling and ablation outcome. Issue 8 (29th June 2020) - Strisciuglio, T; El Haddad, M; Debonnaire, P; De Pooter, J; Demolder, Anthony; Wolf, M; Phlips, T; Kyriakopoulou, M; Almorad, A; Knecht, S; Tavernier, R; Vandekerckhove, Y; et al.
Abstract: Aims: The relation between atrial tachyarrhythmia (ATA) burden in paroxysmal atrial fibrillation (AF), atrial remodelling, and efficacy of catheter ablation (CA) is unknown. We investigated whether high vs. low-burden paroxysmal AF patients have distinct clinical characteristics or electro-mechanical properties of the left atrium (LA) and whether burden impacts outcome of CA. Methods and results: Atrial tachyarrhythmia burden, defined as the percentage of time spent in ATA, was assessed by insertable cardiac monitors in 105 patients before and after CA. Clinical characteristics and electro-mechanical properties of LA were compared between patients with high vs. low ATA burden. Catheter ablation efficacy was assessed by reduction in ATA burden and 1-year freedom from any ATA. Median ATA burden was 2.7% (highest tertile 9.3%). Clinical characteristics and electrical properties of LA (refractoriness, conduction velocity, low voltage) did not differ between high (≥9.3%) vs. low ATA burden (<9.3%) patients. High ATA burden patients had larger LA diameter (46.5 ± 6 vs. 42.5 ± 6mm, P < 0.01), volume (93.8 ± 22 vs. 80.4 ± 21mL, P = 0.01), and lower LA reservoir and contractile strain (19.7 ± 6 vs. 24.7 ± 6%, P < 0.01; 10.3 ± 3 vs. 12.8 ± 4%, P = 0.01). Catheter ablation reduced ATA burden by 100% (100–100) in both groups ( P = 1.0). Freedom from ATA after CA was equally high (83% vs. 89%, P = 0.38). Conclusion: Paroxysmal AF patients with high ATA burden have altered LA mechanical properties, reflected by larger size and impaired function. Despite mechanical remodelling of the atria, they are excellent responders to CA. Most likely the lack of fibrosis and/or advanced electrical remodelling explain why pulmonary veins remain the dominant trigger for AF in this patient cohort.